Geomorphic Characteristics and Morphotectonic Evolution of Karst Depressions on Mount Engizek (Kahramanmaras, Eastern Taurus Mountains) - Seven, Mutlu; Ozturk, Yahya; Gurgoze, Serkan; Ege, Ismail; Tonbul, Saadettin (Tmmob Jeoloji Muhendisleri Odasi, 2025)
Karst plateaus are generally characterized by a dense distribution ofsolution dolines, and the morphometric properties of these dolines can be utilized to determine the morphotectonic characteristics ofkarst plateaus. This study investigated the interrelation between the spatial distribution and morphometric features of karstic depressions on Mount Engizek and the broader morphotectonic evolution of the region. Using topographic maps, Digital Elevation Model (DEM) data, and satellite imagery, a total of 872 karstic depressions (dolines and uvalas) were identified within the mountainous terrain. These depressions were digitized into numerical data by delineating polygons, and their associations with morphotectonic processes were analyzed. In this context, rose diagrams were generated to determine the correspondence between the long-axis orientations of the karstic depressions and structural elements. Morphometric analyses revealed that the average length of the karstic depressions on Mount Engizek is 62 m, while their average width is 41 m, and their approximate surface area is 2,884 m(2). The average elevation of the depressions was calculated as 2,106 m, with an average slope of 12 degrees. Additionally, the mean depth of the depressions was determined to be 8.3 m, and it was found that the area contains an average of five karstic depressions per km(2). The orientation of the mountain follows a NE-SW trend, consistent with NW-SE compression. The morphotectonic evolution of the massif, which shares the same structural trends as the thrust and fold systems within the region, exhibits a structural framework that governs karst processes, as observed throughout the Taurus Mountains. The karstic depressions distributed parallel to the long axis of the summit plateau largely developed under the control of tectono-structural factors. The observed relationship between discontinuity surfaces-such as longitudinal fractures oriented perpendicular to the compression axis and transverse fractures aligned with it-and the development of karstic depressions further substantiates this interpretation.
Keywords: Eastern Taurus Mountains; Mount Engizek; karst depression; tectonics; morphotectonics